1991
DOI: 10.1007/bf00845105
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of hormone therapy, coping skills training, and relaxation for the relief of premenstrual syndrome

Abstract: Approximately 10% of women are severely affected by premenstrual syndrome (PMS) during their reproductive years. Several biological theories of causation have been proposed and each has provoked treatment attempts through medication to little sustained effect. As many of the reported complaints are psychological, a new treatment approach was considered using cognitive-behavioral therapy. A preliminary study which combined cognitive-behavioral therapy with drug treatment produced considerable symptom reduction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…Thus, improvement of mood symptoms and anxiety after DYD administration (18)(19)(20) can be dependent, at least in part, on an increased level of allopregnanolone.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, improvement of mood symptoms and anxiety after DYD administration (18)(19)(20) can be dependent, at least in part, on an increased level of allopregnanolone.…”
Section: Discussionmentioning
confidence: 93%
“…The administration of DYD in fertile women affected by moderate to severe premenstrual syndrome was more effective than placebo against psychological symptoms such as anxiety, tension, and irritability (18). The reduction of anxiety scores in postmenopausal women was greater in those receiving a sequential regimen of transdermal estradiol plus DYD than in those receiving norethisterone acetate (NETA) or nomegestrol acetate (NMA) (19), without affecting negatively the reduction of the depression score induced by the administration of estradiol (20).…”
Section: Discussionmentioning
confidence: 99%
“…10 These treatments and other psychosocial interventions including cognitive therapy, exercise and relaxation deserve further study. 10,11 Evidence suggests that serotonin may play an important role in the pathophysiology of PMS. [12][13][14] But other neurotransmitters and neuromodulators, in particular the gammaaminobutyric acid (GABA), adrenergic, and opioid systems, have also been implicated in the pathophysiology of PMS and PMDD.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that women utilizing CBT with relaxation instructions had significantly reduced PMS symptoms compared with women randomized to a non-active control group during two menstrual cycles [19].…”
Section: Discussionmentioning
confidence: 98%